The impact of linguistic complexity on feasibility and reliability of language mapping in aphasic glioma patients - Kram, Leonie; Neu, Beate; Ohlerth, Ann-Katrin; Schroeder, Axel; Meyer, Bernhard; Krieg, Sandro; Ille, Sebastian (Brain and language, 2025)
Background - Reliable language mappings require sufficient language skills. This study evaluated whether linguistic task properties impact feasibility and reliability of navigated transcranial magnetic stimulation (nTMS)-based language mappings in aphasic glioma patients. - Methods - The effect of linguistic complexity on naming accuracy during baseline testing without stimulation and on the number of errors during nTMS was evaluated for 16 moderately and 4 severely expressive aphasic patients. - Result - During baseline, items acquired later in life and used less frequently, a higher amount of multisyllabic, compound, and inanimate items were named inaccurately. Even after removing these more complex items, less frequent and multisyllabic items were more error-prone during stimulation. - Conclusion - Higher linguistic item complexity was associated with decreased naming accuracy during baseline and resulted in a potentially higher false positive rate during nTMS in aphasic glioma patients. Thus, tailoring task complexity to individual performance capabilities may considerably support the preservation of residual functionality.